2016
DOI: 10.1111/gcb.13498
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected release of phosphate and organic carbon to streams linked to declining nitrogen depositions

Abstract: Reductions in emissions have successfully led to a regional decline in atmospheric nitrogen depositions over the past 20 years. By analyzing long-term data from 110 mountainous streams draining into German drinking water reservoirs, nitrate concentrations indeed declined in the majority of catchments. Furthermore, our meta-analysis indicates that the declining nitrate levels are linked to the release of dissolved iron to streams likely due to a reductive dissolution of iron(III) minerals in riparian wetland so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
65
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 75 publications
7
65
0
Order By: Relevance
“…However in the present study, high SRP during low flow was also observed in headwater catchments free of point-source contributions, and this phenomenon was more prominent in the headwater catchments with the presence of riparian hydromorphic soils (US-Agr and US-For). In independent (mostly forested) catchments located in low mountain areas in Germany, Musolff et al (2016b) have observed that summer SRP release was associated with iron release, suggesting that iron colloids could be a vector of SRP. Musolff et al (2016b) also showed that DOC was closely associated with SRP transfer, similar to observations in US-Agr and US-For.…”
Section: In-stream Processes and Point-source Contributionsmentioning
confidence: 97%
See 1 more Smart Citation
“…However in the present study, high SRP during low flow was also observed in headwater catchments free of point-source contributions, and this phenomenon was more prominent in the headwater catchments with the presence of riparian hydromorphic soils (US-Agr and US-For). In independent (mostly forested) catchments located in low mountain areas in Germany, Musolff et al (2016b) have observed that summer SRP release was associated with iron release, suggesting that iron colloids could be a vector of SRP. Musolff et al (2016b) also showed that DOC was closely associated with SRP transfer, similar to observations in US-Agr and US-For.…”
Section: In-stream Processes and Point-source Contributionsmentioning
confidence: 97%
“…In independent (mostly forested) catchments located in low mountain areas in Germany, Musolff et al (2016b) have observed that summer SRP release was associated with iron release, suggesting that iron colloids could be a vector of SRP. Musolff et al (2016b) also showed that DOC was closely associated with SRP transfer, similar to observations in US-Agr and US-For. Hence, a biogeochemical process taking place in the riparian zone could release SRP during the summer low flow in headwater catchments, mimicking a point-source signal in downstream reaches.…”
Section: In-stream Processes and Point-source Contributionsmentioning
confidence: 97%
“…Musolff et al. () recently offered another, mono‐causal explanation for the increase in DOC in reservoirs of Germany. They suggest that decreasing atmospheric N deposition has triggered increasing dissimilatory reduction and dissolution of Fe oxides in riparian zone soil, which has caused the release of sorbed organic matter (as well as release of sorbed phosphate).…”
mentioning
confidence: 99%
“…The study by Musolff et al. () is based on the statistical evaluation of data compiled from 110 streams draining into 36 German reservoirs, showing parallel increases in Fe and DOC. The authors proposed that the mobilization of 1 mg C results from the reductive dissolution of 0.12 mg Fe (molar OC:Fe ratio: 39).…”
mentioning
confidence: 99%
See 1 more Smart Citation